Rumex japonicus Houtt. alleviates dextran sulfate sodium-induced colitis by protecting tight junctions in mice - Hee-Young Kim; Hyongjun Jeon; Chang Hwan Bae; Yukyoung Lee; Hyungwoo Kim; Seungtae Kim (Integrative Medicine Research)
Background: Rumex japonicus Houtt. (RJ) is widely distributed in Korea, Japan, and China. The root of RJ has traditionally been used to treat constipation, jaundice, hematemesis, dysfunctional uterine bleeding, and gastrointestinal diseases. According to recent studies, plants of the genus Rumex have beneficial functionalities such as anti-microbial, antioxidative, and anti-inflammatory effects. Inflammatory bowel disease, including Crohn's disease and ulcerative colitis, is a chronic inflammatory disease characterized by an abnormal immune response and epithelial barrier dysfunction. This study evaluates the protective effect of RJ against dextran sulfate sodium (DSS)-induced colitis. Methods: Male 8-week-old C57BL/6 N mice were treated with methanolic extract of RJ for 14 days, and DSS-induced groups were administered 2.5% DSS for last 7 days. After sacrifice, the length and weight of the colon were measured, and colon sections were subjected to H&E staining, immunohistochemistry and Western blotting to investigate the changes of inflammatory cytokines, tight junction and apoptosis-related factors. Results: The colon of DSS-treated mouse was significantly shorter and heavier than the normal mouse. Moreover, DSS exposure induced an increase of tumor necrosis factor-α, interleukin (IL)-1β, IL-6, occludin, zonula occludens-1, p21, p53 and Bcl-2, and decreased the expressions of IL-10, claudin-2 and cleaved caspase-3 in the colon tissue. These DSS-induced changes were inhibited by RJ treatment. Conclusion: Our results indicate that RJ effectively suppresses DSS-induced colitis by protecting tight junction connections in the colonic tissue. We therefore infer that RJ has the potential as a medicine or ingredient for treating colitis.